Enhanced Metabolite Productivity of Escherichia coli Adapted to Glucose M9 Minimal Medium - Rugbjerg, Peter; Feist, Adam M.; Sommer, Morten Otto Alexander (Frontiers in Bioengineering and Biotechnology, 2018)
High productivity of biotechnological strains is important to industrial fermentation processes and can be constrained by precursor availability and substrate uptake rate. Adaptive laboratory evolution of E. coli MG1655 to glucose minimal M9 medium has been shown to increase strain fitness, mainly through a key mutation in the transcriptional regulator rpoB, which increases flux through central carbon metabolism and the glucose uptake rate. We wanted to test the hypothesis that a substrate uptake enhancing rpoB mutation can translate to increased productivity in a strain possessing a heterologous metabolite pathway. When engineered for heterologous mevalonate production, we found that E. coli rpoB E672K strains displayed 114-167% higher glucose uptake rates and 48-77% higher mevalonate productivities in glucose minimal M9 medium. This improvement in heterologous mevalonate productivity of rpoB E672K is likely mediated by the elevated glucose uptake rate of such strains, which favors overflow metabolism towards acetate production and availability of acetyl-CoA as substrate. These results demonstrate the utility of adaptive laboratory evolution to generate a platform strain for an increased production rate for a heterologous product.